Eye detection - Nurul Asmira, Ahmad Agin (2009)
Eye detection is a process where the position of the eyes is extracted from the face images. Eye detection is one of the applications in image processing. This project is important in human identification and it can improve today’s identification technique that only involves the fingerprint to identify people. This eye detection is applicable in security system and drowsiness detection. This technology is still new and only few systems are applying this system as their security system. The most crucial part in eye detection system is to identify the eye location. This system is focus on four major parts of preprocessing phase which are image enhancement using median filtering, threshold process, feature extraction and the face and eye detection. This system used an offline face image database. The frontal face image is fed to the system which threshold the image to convert the image into binary image. This process produced an enhanced image after the filtering process. After these preprocessing, feature extraction process is performed to produces the features of the binary image. The face region is determined using rectangular function in MATLAB to limit the range of image to be process and to reduce the noise. Next, the eyes are detected using the morphology technique. A dilation technique is applied to build the square using the structuring element. The eye is view in a square region. Finally, the graphical user interfaces is designed to display the output image.